Correlation Between History of Type of Childbirth and Early Initiation of Breastfeeding with Exclusive Breastfeeding - Farica Emiliana; Koekoeh Hardjito; Ira Titisari; Rahajeng Siti Nur Rahmawati (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2023)
Exclusive breastfeeding means breastfeeding until six months of age with no other additives except vitamins and medicine. Exclusive breastfeeding coverage in Kediri District (34.30%) is still below the national target (45%). Low breastfeeding coverage rates are influenced by many factors, including the history of childbirth and early initiation of breastfeeding. To prevent problems due to the failure of exclusive breastfeeding, this study was conducted to determine the relationship between the history of childbirth and early initiation of breastfeeding with exclusive breastfeeding. The sample size of the research was 49 respondents. The sampling method for this study used simple random sampling. The statistical test of chi square is used for data analysis. The results showed that most respondents had a history of spontaneous labor (69.4%) and early initiation of breastfeeding (69.4%), and also most respondents provided exclusive breastfeeding (51%). Statistical tests showed that there was no correlation between history of childbirth and exclusive breastfeeding (P 0.051) and there was a correlation between and early initiation of breastfeeding and exclusive breastfeeding (P 0.010). Therefore, it has been found that mothers who received early initiation of breastfeeding measures had a greater chance of being able to provide exclusive breastfeeding. Through early initiation of breastfeeding, babies were able to learn to suckle and become accustomed to sucking on nipples, and also helping mothers to prepare their bodies to produce breast milk so they could start providing breast milk to their babies as early as possible and increasing the chances of successful exclusive breastfeeding.